The Use of Doppler Ultrasound to Diagnose Deep Vein Thrombosis of the Lower Limbs - Hussein, Nagla; Khalid, Mohamed (British Journal of Healthcare and Medical Research, 2021)
In most cases of pulmonary embolism, death occurs as a result of deep vein thrombosis (DVT) of the lower extremities. Therefore, to avoid DVT complications and sequel, DVT must be diagnosed as early as possible and this can be achieved via B-mode and colour Doppler imaging. The present paper seeks to investigate the suitability of the imaging method of ultrasound for lower extremity DVT diagnosis and to explore the outcomes of the use of this method in DVT cases. To this end, the paper undertakes a retrospective descriptive study of 50 cases of ultrasound-based diagnosis of DVT at King Khalid Hospital in the period between January 2019 and August 2020. Half of the cases were subjected to compression, colour, and duplex ultrasound, 14 cases were subjected to compression and duplex ultrasound, and 11 cases were subjected to compression and colour Doppler. The mean age across all cases was 46.2±19.9 years. The majority of cases (56%) were in the age range 22-41 years old (n=28), while 28% of cases were in the age range 42-61 years old (n=14), 6% of cases were in the age range 62-81 years old (n=3), and 10% of cases were in the age range 82-102 years old (n=5). Regarding sex, females accounted for 60% of cases, while males accounted for the rest of 40%. Furthermore, in 90% of cases (n=45), just one lower extremity was affected, whereas in 10% of cases (n=5), both lower extremities were affected. Regarding thrombus location, it was found mostly in the area above the knee, particularly the popliteal vein (34%), common femoral vein (18%), and superficial femoral vein (20%). Moreover, 2% of cases presented thrombus in the calf vein. In 26% of cases, multiple veins were affected. DVT was acute in 76% of cases (n=38) and chronic in 24% of cases (n=12). It is concluded that symptomatic and at-risk cases benefit from the use of ultrasound for DVT diagnosis. The suitability of this method stems from its lack of invasiveness and capability to assess thrombus location, magnitude, and stage.